Implementasi Metode TOPSIS untuk Rekomendasi dalam Menentukan Pengadaan Barang pada PT. Sentra Kemika Persada - Steven; Setiawan, Vincent; Agung, Halim (Institut Teknologi dan Bisnis Kalbis, 2019)
PT. Sentra Kemika Persada is a company engaged in chemicals. PT. Sentra Kemika Persada is one of the importers and distributors of chemicals in Indonesia. So far, the decision to procure chemical goods at PT. Sentra Kemika Persada is still done manually, which is only by estimating the need for procurement of goods in the future without a clear or approximate calculation. In addition, checking the stock in the warehouse is still done manually, so it is difficult to get real time inventory reports and determine when PT. Sentra Kemika Persada must procure chemicals. The algorithm used in this study is TOPSIS with an accuracy rate of 75% and an error rate of 25%